The Value of Groups - Hargreaves Heap, Shaun P; Zizzo, Daniel John (American Economic Review, 2009)
We present the results of an experiment that attempts to measure the social value of groups. In the experiment, group membership is induced artificially: subjects interact with insiders and outsiders in trust games and periodically enter markets where they can trade group membership. We find that trust falls with groups because of negative discrimination against outsiders. Against this, however, there is evidence that group membership provides a psychological benefit, albeit one that may induce social inertia. Overall, the welfare effects of groups are at best neutral and could be negative. (JEL: D17, Z13)